How Multinational Corporations Use Information Technology to Manage Global Operations. Issue 2 (3rd April 2017) - Whitaker, Jonathan; Ekman, Peter; Thompson, Steve
ABSTRACT: Despite a generally acknowledged importance of information technology (IT) in enabling global strategy and a broad understanding of the manner in which IT enhances coordination and reduces cost, few studies have focused precisely on how multinational corporations (MNCs) use IT to facilitate globalization. To address this gap in the literature, we conduct a case study across four large MNCs, and use primary data to develop predictive propositions on the characteristics of products, processes, and customers that impact the ways in which MNCs use IT to manage their global operations.